Dynamic impact of cellulose and readily biodegradable substrate on oxygen transfer efficiency in sequencing batch reactors. (15th February 2021) - Ahmed, Ahmed Shawki; Khalil, Ahmed; Ito, Yuichi; van Loosdrecht, Mark C.M.; Santoro, Domenico; Rosso, Diego; Nakhla, George
Highlights: α-factor decreased by 48% and 19% due to the addition of acetate and cellulose. The absence of active biomass decreased α-factor by 45%. An inverse correlation between α-factor and sCOD was defined. Cellulose hydrolysis was fast with a first-order hydrolysis coefficient of 4.1 d  − 1. RBF selectively removed cellulose thus reducing aeration energy by 25%. Abstract: Aeration is a major contributor to the high energy demand in municipal wastewater treatment plants. Thus, it is important to understand the dynamic impact of wastewater characteristics on oxygen transfer efficiency to develop suitable control strategies for minimizing energy consumption since aeration efficiency is influenced by the biodegradation of pollutants in the influent. The real-time impact of acetate as a readily biodegradable substrate and cellulose as a slowly biodegradable substrate were studied at different operational conditions. Cellulose in the influent wastewater can be removed efficiently using primary treatment technologies, such as the rotating belt filter (RBF). At an ambient DO of 2 mg l −1 and air flow of 1.02 m 3 h −1 (0.6 SCFM), the α-factor was more sensitive to readily biodegradable substrates than to cellulose. On average, α-factor decreased by 48% and 19% due to the addition of acetate and cellulose, respectively. At a DO of 4 mg l −1 and air flow of 1.7 m 3 h −1 (1 SCFM), α-factor remained constant irrespective of cellulose and acetate concentrations. Without active biomass, α-factor decreased by 47% and 43% at a DO of 2 mg l −1 (air flow of 1.02 m 3 h −1 ) and high DO of 5 mg l −1 (air flow of 1.7 m 3 h −1 ), respectively. An inverse correlation between α-factor and sCOD was defined and incorporated into a dynamic model to estimate the real-time airflow rates associated with the improvement of the oxygen transfer efficiency due to biodegradation. Finally, the RBF operated with a 158-μm mesh selectively removed cellulose, thus reducing air requirements, and energy by 25%. Graphical abstract: Image, graphical abstract